P45 Regional comparison of socioeconomic and environmental profiles of families with pregnant women in the All Ireland Traveller Health Study. (16th November 2010) - Hamid, N A; Abdalla, S; Turner, J; Quirke, B; Niccharthaigh, R; Kelleher, C; Fitzpatrick, P; ,
Abstract : Objective: Travellers have been documented as a distinct group in Irish society for centuries. They experience significant socio-economic and health disadvantage particularly pertinent to pregnancy and early childhood development. This analysis contrasts the socio-economic and environmental profiles of "families with a resident pregnant woman" (FRPW) to other Traveller families and according to two distinct geopolitical regions. Setting: Census survey of the All Ireland Traveller Health Status Study of 10 618 Traveller families in the Republic of Ireland (ROI) and Northern Ireland (NI). Methodology: Cross-sectional descriptive analysis of all FRPW in recruitment stage of prospective birth cohort study. Results: General comparison of socio-economic indicators showed marked differences between regions. There were 42 FRPW in NI (2.7% of all census families), 670 (7.4%) in ROI. FRPW family size was smaller in NI (mean 2.7, median 2, SD 1.9) compared to ROI (mean 4.1, median 4, SD 2.6) (p=0.001). Literacy rate was better in FRPW compared to non-FRPW in ROI but not in NI. However, there were no differences in literacy and numeracy rates for FRPW between regions. More FRPW in NI than ROI live in caravan/mobile home/trailer (40.5% NI vs 20% ROI, p<0.001); stayed for shorter period in their current accommodation (47.6% NI vs 33.5% ROI, p=0.002) and were forced to move by local community (12.2% NI vs 2.6% ROI, p<0.001). FRPW in NI have better private transport ownership (83.3% vs 79.6% ROI, p<0.001). There was a greater lack of general public facilities for example, working public lighting and fire hydrants, and more problems with living environment for example, lodged water (22.9% ROI vs 10% NI) and living near a road side (48.4% ROI vs 35% NI) (all p<0.001) in ROI compared to NI. These varied across the type of accommodation and may be associated with poor quality living accommodation. There was a significant difference in the reporting of perceived "very unhealthy/unhealthy" (40.5% NI vs 25.3% ROI; p<0.001) and "very unsafe/unsafe" (40.5% NI vs 27.3% ROI) living environment. Conclusion: FRPW suffer from different socioeconomic and environmental amenity disadvantages in the regions; such differences may reflect overall regional differences rather than be related specifically to pregnancy. In both jurisdictions health needs are considerable with significant policy indications.